Broad resistance of RD6 introgression lines with xa5 gene from IR62266 rice variety to bacterial leaf blight disease for rice production in Northeastern Thailand - Wongkhamchan, Apiluk; Chankaew, Sompong; Monkham, Tidarat; Saksirirat, Weerasak; Sanitchon, Jirawat (Agriculture and Natural Resources, 2018)
This study focused on the transferred xa5 gene from the rice cultivar IR62266 into the genome of the RD6 cultivar for bacterial leaf blight (BLB) resistance using the marker-assisted backcrossing method. Ten RD6 introgression lines were selected from the BC2F2:3 population. The RD6 introgression lines and their parents were evaluated for BLB resistance using 15 isolates of Xanthomonas oryzae pv. oryzae (Xoo) collected from northeastern Thailand. The Xoo isolates were artificially inoculated onto the leaves of the rice cultivars for validation of BLB resistance at the seedling stage. The results showed that there were statistically significant differences in the BLB lesion length among the test cultivars in most of the Xoo isolates. The broad-spectrum resistance values of introgression lines BC2F2:3 1-13-17-52 and BC2F2:3 1-28-8-37 were the same (0.6) and close to that of the resistant cultivar IR62266 (0.67). In further application, the new rice lines (RD6 resistance to BLB) can be used for pyramiding with other traits for blast resistance and drought tolerance combined with desirable agronomic attributes, for the development of an RD6 rice variety.